2006
DOI: 10.1100/tsw.2006.215
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Role of Microbiological Culture and Sensitivity in the Management of Superficial Soft Tissue Abscesses

Abstract: The aim of this study was to assess the role of the routine practice of microbial culture and sensitivity at incision and drainage of superficial soft tissue abscesses. The case notes of 162 consecutive patients, selected from the microbiology database over a period of 1 year, were reviewed. All had incision and drainage of superficial soft tissue abscesses and included perianal, pilonidal, axillary, and breast abscesses. Patients with chronic wounds, recurrent abscesses, diabetes, pregnancy, and immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
(15 reference statements)
3
13
0
Order By: Relevance
“…In this study, the frequency of bacterial growth in swab samples was comparable in patients with pPS (84·93%) and rPS (86·96%), which is in accordance with the findings of Khan et al (80·00%) . Many studies have reported a predominance of anaerobic bacteria in aspirates and swab samples from patients with pPS, reported genera including Bacteroides , Clostridium , Fusobacteria and Prevotella Our findings confirm the predominance of anaerobic bacteria in pPS.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the frequency of bacterial growth in swab samples was comparable in patients with pPS (84·93%) and rPS (86·96%), which is in accordance with the findings of Khan et al (80·00%) . Many studies have reported a predominance of anaerobic bacteria in aspirates and swab samples from patients with pPS, reported genera including Bacteroides , Clostridium , Fusobacteria and Prevotella Our findings confirm the predominance of anaerobic bacteria in pPS.…”
Section: Discussionsupporting
confidence: 91%
“…In this current study, of the 75.4% of patients that had wound swabs taken, 87. [4]. The most common microorganisms identified in culture in this current study was mixed anaerobic microorganisms (61.6%), a finding similar to other studies [3,4].…”
Section: Discussionsupporting
confidence: 91%
“…One retrospective study on all cutaneous abscesses reported that 67.5% of their patients had wound specimens sent to the laboratory from the procedure [5]. Another study reported that 100% of their patients had wound swabs taken at the procedure which was assumed from a microbiology database [4]. In this current study, of the 75.4% of patients that had wound swabs taken, 87.…”
Section: Discussionmentioning
confidence: 58%
“…Forty patients (17.9%) underwent additional surgery. Out of these 40 patients, 28 underwent elective pilonidal sinus surgery following single (23) or recurrent (5) abscess drainage, 10 drainage for recurrent abscess(es) without sinus surgery, and 2 abscess drainage some time after elective sinus surgery. In this general group, additional surgery was not related to gender (P = 0.68) or the site of initial drainage (P = 0.74).…”
Section: Resultsmentioning
confidence: 99%
“…spreading cellulitis, immunocompromised patient), the choice of agent is made prior to knowing the culture results. Studies of other subcutaneous abscesses suggest that knowledge of the usual pathogens guides the clinician to an appropriate antibiotic choice and that antibiotic treatment is rarely changed after reviewing the culture result (even where resistant pathogens are found) [23][24][25]. In those situations where antibiotics are prescribed for patients with a pilonidal abscess, anaerobic cover is essential, but in our patients, this was often omitted.…”
Section: Discussionmentioning
confidence: 97%